Investigating the habits and satisfaction of tourists towards culinary facilities at Manggar Sari Beach, East Kalimantan - Purwaningrum, Hesti (Borneo Novelty Publishing, 2024)
Purpose - This study aims to explore the development of rural tourism in Indonesia, focusing on emerging trends, key challenges, and opportunities for sustainable growth. Methodology/Design/Approach - The research adopts a qualitative review approach, synthesizing recent academic literature, government reports, and case studies related to rural tourism practices in various regions of Indonesia. Findings - The study identifies a growing interest in rural tourism driven by government initiatives and community-based tourism models. However, it also highlights persistent challenges such as limited infrastructure, lack of professional management, inconsistent policy implementation, and the need for stronger local capacity-building. Originality/Value - This paper provides a consolidated overview of the rural tourism landscape in Indonesia, offering insights into both its current state and future potential. It serves as a valuable reference for policymakers, tourism developers, and researchers aiming to support sustainable rural tourism in Indonesia.